The Potential of iPS Cells in Synucleinopathy Research. (18th March 2012) - Linta, Leonhard; Stockmann, Marianne; Boeckers, Tobias M.; Kleger, Alexander; Liebau, Stefan
Abstract : α-synuclein is a protein involved in the pathogenesis of several so-called synucleinopathies including Parkinson's disease. A variety of models have been so far assessed. Human induced pluripotent stem cells provide a patient- and disease-specific model for in vitro studies, pharmacotoxicological screens, and hope for future cell-based therapies. Initial experimental procedures include the harvest of patients' material for the reprogramming process, the investigation of the patients genetic background in the cultured cells, and the evaluation of disease-relevant factors/proteins under various cell culture conditions.